Prognostic significance of preoperative prognostic nutritional index in hepatocellular carcinoma after curative hepatectomy: a meta-analysis and systemic review - Zhang, Haiyan; Li, Dan; Li, Jing (Frontiers in Nutrition, 2024)
BackgroundThe Prognostic Nutritional Index (PNI), which reflects both nutritional and immune status, has emerged as a potential predictor of survival outcomes in cancer patients. However, its role in forecasting the prognosis of hepatocellular carcinoma (HCC) following curative hepatectomy remains unclear. To further investigate the association between PNI and survival outcomes in HCC patients, we conducted a systematic review and meta-analysis.MethodsWe performed a comprehensive search across Web of Science, PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure to identify studies evaluating the prognostic value of PNI in HCC following curative hepatectomy. Overall survival (OS), recurrence-free survival (RFS), and disease-free survival (DFS) were extracted as primary outcomes. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using fixed-effect or random-effect models. Additionally, heterogeneity, publication bias, and sensitivity analyses were performed to evaluate the consistency and robustness of the obtained results.ResultsThis systematic review and meta-analysis included 19 studies comprising a total of 9,830 patients. The results indicated that higher PNI was significantly associated with longer overall survival (OS) (n = 6,812; HR = 1.60; 95% CI: 1.44–1.77; p < 0.001) and recurrence-free survival (RFS) (n = 8,529; HR = 1.48; 95% CI: 1.30–1.69; p < 0.001). There was significant heterogeneity among studies for RFS (I2 = 56.0%, p = 0.004). Subgroup analysis indicated that age, variations in PNI cutoff values and follow-up periods were the primary contributors to this heterogeneity. The trim-and-fill method indicated that publication bias did not impact the OS results, and Egger’s test found no publication bias for RFS (p = 0.104). Sensitivity analysis further confirmed the stability of these results.ConclusionPreoperative PNI is a significant prognostic indicator in HCC patients undergoing curative hepatectomy, with higher PNI correlating with improved survival outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024530150, identifier CRD42024530150.